ASUHAN KEPERAWATAN PADA TN. B DENGAN CHRONIC KIDNEY DISEASE STAGE V ON HD DI RUANG INSTALASI HEMODIALISA D RUMAH SAKIT BHAYANGKARA TK.I R. SAID SUKANTO - Ade Rahmawati (2022)
chronic disease is a disease that can occur because of kidney disorders that toxins or toxic substances that should be released from the kidney become inexcible, resulting in the development of elevated levels of ureum in the body that render neurons and other cells unable to function properly. Purpose: the study is done to gain real experience and picture in nursing care care programs involving studies, nursing diagnosis, nursing plans, the implementation of nursing and nursing evaluations. Method : research design used is a descriptive method in the form of case studies to implement nursing care the chronic disease stage v on hd at kindergarten hospital. I r.said sukanto. Data collection takes place through interviews, observation and physical examination and documentary studies.The result : the treatment problem, given the case, is fluid overload due to regulational mechanism disruption, activity intolerance relating to the imbalance between need and oxygen supply, the risk of collapse relating to anemia. After a 1 24-hour evaluation, all nursing issues have not been resolved. Conclusion : it is hoped that further studies can provide nursing care in patients with chronic disease and correct care to achieve according to the nursing problem discovered in patients.